A SERS-based molecular sensor for selective detection and quantification of copper(II) ions - Dugandzic, Vera; Kupfer, Stephan; Jahn, Martin; Henkel, Thomas; Weber, Karina; Cialla-May, Dana; Popp, Juergen (Sensors and Actuators B-Chemical, 2019)
A novel SERS-based molecular sensor for detection and quantification of copper(II) ions with very good specificity and selectivity is reported in this work. The sensing is enabled by the employment of a synthesized dipicolylamine-based ligand anchored onto plasmonic gold nanoparticles through the sulfur atom of the methylthio group. The interaction of the ligand with copper(II) ions is followed by changes in the spectral features associated with pyridine ring breathing, as indicated by quantum chemical calculations performed at the density functional level of theory, which are proportional to the copper(II) concentration. The detection of copper(II) was possible down to 5 × 10−8 M in water. The proposed molecular sensor was applied for the detection of copper(II) ions in white wine, with the ability to detect amounts of copper(II) in wine lower than the maximum recommended amount of 7.87 × 10−6 M (0.5 μg/mL), indicating that the proposed molecular sensor is of potential interest as a routine test for the control of the copper(II) content in wine during wine production and in the final product.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Copper(II); DFT; Molecular sensor; SERS; Wine